Depositional environment and hydrocarbon source potential of the Lower Miocene oil shale deposit in the Aleksinac Basin (Serbia). (January 2018) - Bechtel, Achim; Oberauer, Klaus; Kostić, Aleksandar; Gratzer, Reinhard; Milisavljević, Vladimir; Aleksić, Nikoleta; Stojanović, Ksenija; Groß, Doris; Sachsenhofer, Reinhard F.
Highlights: Changes in redox conditions and water column stratification are outlined. Carbon cycling in the water column affects δ 13 C values of OM. Immaturity of OM is based on vitrinite reflectance and biomarker ratios. Excellent source rock quality is indicated by TOC and Rock-Eval data. Aleksinac oil shale holds a high quality shale oil potential. Abstract: The most prolific oil shale deposit in Serbia is located in the Aleksinac Basin and is assigned to the Lower Miocene. Depositional environments and hydrocarbon potential were assessed for the Aleksinac oil shale and coal layers through bulk geochemical, organic petrographical, biomarker, and carbon isotope data from core samples from a single well. Maturity parameters (vitrinite reflectance, T max, biomarker isomerisation ratios) prove that the organic matter (OM) is immature. A lower lacustrine oil shale sequence is comprised of alternating sandstone and clay-rich rocks and some thin coal beds, indicating strong variations in depositional environment. This stratum is covered with thick sandstone (50 m) terminated by the main 4 m thick coal seam that was deposited in a low-lying mire, as evidenced by high total sulfur and mineral matrix contents. The plant input was dominated by angiosperms. A relative rise in water level led to the drowning of the swamp and to the deposition of a 60 m thick upper oil shale in a lacustrine environment. The OM of the oil shale is dominated by kerogen Type I (lamalginite). Biomarker data suggest a stratified water column that likely formed due to differences in salinity. The stratified water column led to a strictly anoxic environment and photic zone euxinia in a mesosalinar, hydrologically closed lake, which enabled the accumulation of uncommonly high amounts of organic material (average TOC: 18.0 wt%) with excellent preservation (average HI: 743 mg HC/g TOC).